REVITALISASI PASAR RAKYAT DALAM UPAYA PENINGKATAN SOSIAL EKONOMI PEDAGANG DAN EKSISTENSI PASAR DI PASAR MANDALIKA KOTA MATARAM - Arifin, Muhammad (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
Many efforts have been made by the government to develop and organize people's markets through the revitalization of the people's market, but some of the conditions of the people's market after the revitalization are not as expected. The purpose of this study is to analyze the extent of market conditions, the responses of traders and consumers and their impact on the socio-economics of traders and the existence of the market after the implementation of market revitalization at the Mandalika Market, Mataram City. This study uses a descriptive qualitative method with a case study approach. The data collection process was carried out by means of observation, in-depth interviews, and documentation studies. Data analysis was carried out through data reduction, data presentation and conclusion drawing. While the data validity technique used is triangulation of data sources. The results of the study concluded that the physical condition of the market after the revitalization showed a better improvement even though some market facilities were still incomplete and not in accordance with the requirements, while the management, economic and social revitalization had not been carried out optimally. Traders and consumers responded positively to the market conditions resulting from the revitalization, but some traders responded negatively to the shape and size of the shop which was too small. The social impact of market revitalization on traders has both positive and negative impacts. The positive impact, namely the relationship and interaction between fellow traders in the Mandalika Market is getting better, while the negative impact with traders selling private markets triggers business competition. The resulting economic impact has a negative impact on the decline in the income of market traders, the decreasing number of traders causes the government's income from market levies to also decrease, so that it has the potential to decrease the existence of the market.